1991
DOI: 10.1007/bf00418276
|View full text |Cite
|
Sign up to set email alerts
|

Glucose enhances type IV collagen production in cultured rat glomerular mesangial cells

Abstract: Summary. Type IV collagen production by cultured glomerular mesangial cells and the effect of glucose on it were evaluated in order to explore the possible contribution of mesangial cells to the accumulation of type IV collagen in mesangial matrix typically seen in diabetes. Type IV collagen was measured quantitatively by enzyme-linked immunosorbent assay. The majority of type IV collagen was secreted into culture media and secreted-type IV collagen increased with cell growth in early log phase and decreased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(62 citation statements)
references
References 10 publications
(12 reference statements)
5
57
0
Order By: Relevance
“…Recently, it was reported that proliferating glomerular mesangial cells synthesize extracellular matrix components similar to that seen in the glomerular mesangium in vivo [3]. Furthermore, increased production of collagen type IV [2,3], laminin [3] and fibronectin [3] has been reported in rat mesangial cells when grown in high glucose medium for 12 [2] or 7 [3] days, respectively. The latter observation concerning fibronectin is different from that which we observed and may be due to different experimental design since we measured fibronectin content after short incubation times during the logarithmic phase of growth (48 h).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, it was reported that proliferating glomerular mesangial cells synthesize extracellular matrix components similar to that seen in the glomerular mesangium in vivo [3]. Furthermore, increased production of collagen type IV [2,3], laminin [3] and fibronectin [3] has been reported in rat mesangial cells when grown in high glucose medium for 12 [2] or 7 [3] days, respectively. The latter observation concerning fibronectin is different from that which we observed and may be due to different experimental design since we measured fibronectin content after short incubation times during the logarithmic phase of growth (48 h).…”
Section: Discussionmentioning
confidence: 93%
“…Changes of mesangial matrix composition in diabetes mellitus have been reported recently [1]. Especially, increased synthesis of collagen type IV [2] and other matrix constituents [3] have been demonstrated in rat mesangial cells cultured in high glucose medium. Basement membrane associated heparan sulphate proteoglycan (HSPG) is believed to play a key role in the development of diabetic glomerulopathy.…”
mentioning
confidence: 99%
“…This difference in tissue response may reflect the constellation of cells present in myocardial capillaries (endothelial cells and pericytes) and glo-meruli, which contain epithelial cells in addition to endothelial and mesangial cells; previous studies from our laboratory have indicated that only the latter two cell types form type VI collagen, while all three synthesize type IV. Most previous investigations on the effect of glucose on collagen synthesis by cells in culture have focused on type IV and have found an approximately twofold increase in this protein, whether the elevated glucose was present during the entire growth period of endothelial [17,26] or mesangial [27][28][29] cells or when exposure of confluent glomerular epithelial, mesangial or endothelial cells was only for short periods of time [3,6]. The influence of elevated glucose on type VI collagen has previously been studied only with rat glomerular mesangial cells and in that system the extent of stimulation was similar for both types VI and IV collagens, even though marked differences were observed in other aspects of the response, with type VI reflecting more rapidly both increased and normalized glucose levels, and only type IV being enhanced by addition of the glucose metabolite pyruvate or by the presence of aldosterone or IGF-1 [3].…”
Section: Discussionmentioning
confidence: 99%
“…Since our previous studies [6,7] and those of others [40,41] have indicated that high glucose initiates a series of events in mesangial cells which lead to the accelerated production of matrix components, the occurrence of two separate mechanisms of glucose entry provides expanded possibilities for regulation and channelling of metabolites. While it is generally appreciated that Na + can be the driving force in promoting the uptake of glucose by cells which have a coupled transporter, and indeed we have previously observed that in mesangial cells this ion stimulates glucose consumption as well as collagen synthesis [7], the converse of this mechanism, namely the enhancement of Na + flux by glucose, is rarely considered even though it has been experimentally demonstrated to occur in renal brush border membrane vesicles [42].…”
Section: Rna+-dependent ~ ~ Facilitativementioning
confidence: 97%